TIBIAL PLATEAU FRACTURES: FUNCTIONAL OUTCOME EVALUATION OF OPEN REDUCTION AND INTERNAL FIXATION TECHNIQUES - Muhammad Azfar Khanzada 1, Muhammad Tahir Lakho2, Zulfiqar Ali Memon3, Safiya Javed4, Syed Alam Zeb5, Bashir Ahmed6., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
ABSTRACT OBJECTIVE: To evaluate the functional outcome of open reduction and internal fixation surgical technique used in different types of tibial plateau fractures among patients in Hyderabad, Pakistan. METHODOLOGY: Prospective study was conducted from September 2018 to September2019 on patients presented with injuries and fractures involving knee joint admitted in the orthopedic unit of Liaquat University Hospital, Hyderabad. Patients > 18 years of age, either gender, having fracture involving knee joint, having confirmed tibial plateau fracture were included. Pre-operative X-ray upper tibia and/or distal femur of the affected limb of all the patients followed by Computed Tomography scan with or without 3D were performed. Open or closed reduction and internal fixation were performed. The functional outcome of the participant was assessed through the Knee Society Score. Data was analyzed using student’s t-test in SPSS ver. 22. RESULTS: Most common mode of injury was fall followed by road traffic accidents (41.25%).There was a statistically significant difference in functional mobility score between the age groups and gender (p < 0.05).While the statistically significant (p < 0.05) decline in mean Knee Society Score was observed in participants who had been bearing full weight for 3 months. CONCLUSION: Tibial plateau fractures are commonly occurring among males and usually resulting due to road traffic accidents. Early knee mobilization and consequent good mid- to long-term functional results, open or closed reduction, as well as stable internal fixation, is the treatment of choice.